The house of Dimon : how JP Morgan's Jamie Dimon rose to the top of the financial world - Crisafulli, Patricia (Hoboken, N.J. : Wiley, 2009)
The author, Crisafulli accomplished a major feat by gleaning the lessons-to-be-learned from the life thus far of Jamie Dimon, a man of extraordinary talent, rock-solid philosophy of life, and boundless energy, as well as capturing the essence of many of the financial industry's key personalities, explaining in layman's terms the financial instruments, environment, and events of the last two decades.
"With new post-crisis update"--Cover.
"Paperback edition"--P. xv.
Originally published: 2009.
Includes bibliographical references (p. 219-232) and index.
rua 25/04/13
Loans
Keywords: Dimon, Jamie; J.P. Morgan Chase & Co; Capitalists and financiers -- United States -- Biography